PRESERVASI PERKERASAN LENTUR BERDASARKAN NILAI KONDISI JALAN MENGGUNAKAN METODE PCI DI JALAN SRIKANDI KOTA PEKANBARU - Edi Yusuf Adiman; Rizqy Ridho Praksa; Ridwan Frestantio; Aulia Akbar Nadim; Ahmad Rilwanu Ribbiyuan; Khairul Amri (Racic : Rab Construction Research, 2023)
Pavement preservation in urban areas can increase population mobility. So that the road maintenance treatments are not only concentrated on arterial roads. This research aims to determine the road conditions and preservation treatments of flexible pavement on one of the collector roads in Pekanbaru City, that's on Srikandi Street. Types of distress in flexible pavements were obtained by visual survey at the location. The road is divided into 12 sections, where each section is 200 meters apart. Pavement condition assessment method using the Pavement Condition Index (PCI). The results of the pavement condition assessment analysis, the PCI average on Srikandi Street is 72.75 (satisfactory). Pavement preservation activity required on Srikandi Street is routine maintenance on sections 1, 3, 4, 6, 7, 8, and 10, with the treatment by patching, leveling, crack sealing, and sealcoating; preventive maintenance on sections 2, 5, 9, and 11, with the treatment by nonstructural overlay using a Thin Hot Mix Asphalt (THMA); and pavement rehabilitation in section 12, with the treatment by mill and inlay.